Visitor characteristics and changes in mental health stigma after attending the Mind Space mental health experience exhibition - Ho, Grace W. K.; Mui, Jolene Hang Chun; Wong, Raymond; Chien, Wai Tong; Wong, Kwan Ho; Bressington, Daniel (Frontiers in Psychiatry, 2024)
Mind Space is an experiential mental health exhibition in Hong Kong, aiming to raise public awareness and provide education regarding mental health. This pre-post study aimed to 1) examine the relationships between visitors' characteristics and their mental health stigma at baseline, and 2) provide a preliminary evaluation of the effectiveness of Mind Space in reducing stigma and promoting help-seeking attitudes towards mental health conditions. We analyzed data from all consenting visitors who attended Mind Space between September 2019 and December 2021. Visitors' attitudes towards mental health conditions and their willingness to seek professional psychological help were measured through online questionnaires before and after visits.Multiple linear regression was used to identify the demographic predictors of outcome variables at baseline. Changes in outcome variables after attending Mind Space were assessed using paired sample t-tests. A total of 382 visitors completed the baseline questionnaires, among which 146 also completed the post-test. At baseline, higher socioeconomic levels and personal contact with people with mental health conditions predicted more positive attitudes and understanding towards mental disorders.Tentatively, the results also showed that after attending Mind Space, a significant reduction in negative attitudes about mental illness (t=4.36, p=<.001; d=.361) and improvements in the propensity to seek professional help (t=-5.20, p<.001; d=-.430) were observed, along with decreases in negative attitudes toward stereotypes (t=4.71, p=<.001; d=.421) and restrictions (t=2.29, p=.024; d=.205) among healthcare professionals. Our findings highlight the need for mental health education for people with lower socioeconomic status and the importance of direct contact in public mental health education initiatives. The present study also suggests that Mind Space may be a useful model for public mental health education, but the exhibition requires further evaluation to ascertain if any reductions in stigma are maintained over time.